2015
DOI: 10.1002/pds.3744
|View full text |Cite
|
Sign up to set email alerts
|

Does the average drug exposure in pregnant women affect pregnancy outcome? A comparison of two approaches to estimate the baseline risks of adverse pregnancy outcome

Abstract: This study does not provide evidence for an increased risk of adverse pregnancy outcome after average drug exposure during pregnancy. Therefore, comparison cohorts with average drug exposure are appropriate for studies on potential teratogens or fetotoxicants based on observational data collected by TIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Therefore, the control group does not necessarily represent the general pregnant population but rather a subset of particularly concerned and/or health-oriented patients with non-teratogenic drug exposure. A recent publication demonstrated that this approach does not substantially bias the results of pregnancy outcome studies [47].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, the control group does not necessarily represent the general pregnant population but rather a subset of particularly concerned and/or health-oriented patients with non-teratogenic drug exposure. A recent publication demonstrated that this approach does not substantially bias the results of pregnancy outcome studies [47].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The usage of drugs show massive regional variations, hence, different drug utilization patterns can be observed . In comparison with German databases, lower intake was detected in this study . However, most of the drug utilization information was obtained by questionnaires or prescription data and not by bio monitoring as in this study.…”
Section: Discussionmentioning
confidence: 57%
“…3,[12][13][14] In comparison with German databases, lower intake was detected in this study. 6 However, most of the drug utilization information was obtained by questionnaires or prescription data and not by bio monitoring as in this study. All monitoring methods provide pros and cons: recall biases are common in questionnaires leading to false negative results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations